Complete pathological response of high grade appendicular neoplasm induced Pseudomyxoma Peritonei (PMP) after neoadjuvant intra-peritoneal chemotherapy: A case report. (2020) - Padmanabhan, Naveen; Ishibashi, Haruaki; Nishihara, Kazurou; Sako, Shouzou; Katayama, Kanji; Wakama, Satoshi; Kamada, Yasuyuki; Yonemura, Yutaka
Highlights: Completeness of cytoreduction is the key factor for long term survival in pseudomyxoma peritonei. Neoadjuvant chemotherapy for unresectable cases of PMP has been tried but often with discouraging results. Intraperitoneal administration of chemotherapy can result in higher drug concentrations in the peritoneal cavity. A seventy two year old lady presented with extensive bulky PMP received laparoscopy, Extensive Intraperitoneal lavage and Intraperitoneal chemoport insertion. After 12 sessions of NIPT, she had complete resolution of disease and was treated with complete cytoreductive surgery with peritonectomies and Hyperthermic Intraperitoneal chemotherapy with oxaliplatin and 5-Fluorouracil. Pathologic examination showed only mucin and no atypical or neoplastic cells. Abstract: Background: Pseudomyxoma Peritonei (PMP) is clinical syndrome characterized by mucinous ascites and gelatinous tumor deposits in the peritoneal cavity. Complete Cytoreduction and Hyperthermic intraperitoneal perfusion is the contemporary standard of care for PMP. A novel treatment approach with Intraperitoneal (IP) chemotherapy has been developed for patients with disease not amenable for complete cytoreduction. Case presentation: A 72 year old lady had PMP arising from high grade appendicular neoplasm with extensive intraabdominal spread not suitable for complete cytoreduction (PCI -19; multiple mesenteric deposits). Novel approach with tumor debulking and Neoadjuvant Intraperitoneal chemotherapy was done. Excellent clinical response was obtained after 12 sessions of IP chemotherapy with cisplatin and docetaxel. Subsequently she underwent Complete cytoreductive surgery with peritonectomy and Hyperthermic intraperitoneal chemotherapy. Pathological examination of surgical specimens revealed only acellular mucin with no viable tumor cells indicating a complete response. Discussion: Complete pathological response after IP chemotherapy in extensive PMP is rare. Nevertheless the results are encouraging as the systemic therapy hasn't yielded successful outcomes. IP chemotherapy has the advantage of achieving high intraperitoneal concentrations and down staging the tumor spread. Conclusion: Neoadjuvant Intra-peritoneal chemotherapy is a promising neoadjuvant strategy in patients who are poor candidates for upfront resection due to extent of disease or performance status, perhaps better than systemic therapy.